Pengaruh Ekstrak Daun Salam Terhadap Gambaran Histopatologi Pankreas Tikus Wistar Model Diabetes Melitus - Winny Angela Tionando (Faculty of Medicine, Universitas Andalas, 2021)
Objective: the purpose of this study was to determine the histopathological description of the pancreas of Wistar rats with diabetes melitus model which were given bay leaf extract at various doses; Method: this type of research used an experimental design with a pretest – posttest randomized control group design. The samples used were 24 rats divided into 4 groups: normal control, negative control, treatment 1 (given extract 100 mg/kgBW), treatment 2 (given extract 200mg/kgBW); Result: after being monitored for 14 days, there was a decrease in blood sugar levels in rats given an extract dose of 100 mg/kgBW (109.17±45.86 mg/dL) and extract dose of 200 mg/kgBW (79.83±19.78 mg/dL) and in the group of rats which were given bay leaf extract, there was an improvement in pancreatic tissue; Conclusion: statistically and microscopically, it was found that bay leaf extract at a dose of 200 mg/kgBW was more effective in lowering blood sugar levels and regenerating pancreatic tissue in Wistar rats.